Subtypes of GABAergic neurons project axons in the neocortex - Higo, Shigeyoshi; Akashi, Kaori; Sakimura, Kenji; Tamamaki, Nobuaki (Frontiers in Neuroanatomy, 2009)
γ-aminobutyric acid (GABA)ergic neurons in the neocortex have been regarded as interneurons and speculated to modulate the activity of neurons locally. Recently, however, several experiments revealed that neuronal nitric oxide synthase (nNOS)-positive GABAergic neurons project cortico-cortically with long axons. In this study, we illustrate Golgi-like images of the nNOS-positive GABAergic neurons using a nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d) reaction and follow the emanating axon branches in cat brain sections. These axon branches projected cortico-cortically with other non-labeled arcuate fibers, contra-laterally via the corpus callosum and anterior commissure. The labeled fibers were not limited to the neocortex but found also in the fimbria of the hippocampus. In order to have additional information on these GABAergic neuron projections, we investigated green fluorescent protein (GFP)-labeled GABAergic neurons in GAD67-Cre knock-in / GFP Cre-reporter mice. GFP-labeled axons emanate densely, especially in the fimbria, a small number in the anterior commissure, and very sparsely in the corpus callosum. These two different approaches confirm that not only nNOS-positive GABAergic neurons but also other subtypes of GABAergic neurons project long axons in the cerebral cortex and are in a position to be involved in information processing.